Dosimetry Characteristic of Co-60 Calibration Source in SSDL Jakarta Facility After Source Replacement - Assef Firnando Firmansyah; Okky Agassy Firmansyah; Sri Inang sunaryati (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2021)
Secondary Standard Dosimetry Laboratory (SSDL) Jakarta's main task is to maintain the traceability of ionizing radiation units in Indonesia. One of their public services is calibration for nuclear instruments for therapy, consisting of dosimeter calibration and radiotherapy machine output. In the early of 2020, the dosimeter's calibration facilities have been out of date. The replacement of the Co-60 machine was done with a new one. However, the Co-60 machine re-used the Co-60 machine from Hospital radioactive nuclear waste. This paper discusses the dosimetric characteristic of the reusable Co-60 machine as a calibrator machine. Measurement data consisted of timer error, beam center and profile, dose rate in air Kerma and absorbed dose rate to water, and decaying stability. The reference used for measurement was IAEA Publication TRS No. 469. All measurement was taken by standard ionization chamber. The timer error result shows -2.52 seconds delayed after switching on the machine. The air Kerma rate was obtained at 230.15 µGy/min, meanwhile for absorbed dose rate to water was obtained 211.08 mGy/min. The source activity was monitored at 51.4 TBq on Dec 07, 2020. The decays of activity and dose rate were lies in the acceptable range. It should be lies on the 20 – 40 TBq for activity, meanwhile for dose rate should more than 100 mGy/min at 1 m distance. The stability was covered up in terms of dose rate and maintained in one percent deviation limit. Based on the result, this reusable Co-60 machine is ready to use as a calibrator source in gamma-ray facilities.                                                    Keywords: Co-60 machine, calibration, SSDL, metrology, ionizing radiation ABSTRAK             Tugas utama Laboratorium Dosimetri Standar Sekunder (SSDL) Jakarta adalah untuk menjaga ketertelusuran kalibrasi dari besaran radiasi pengion di Indonesia. Salah satu layanan publik yang disediakan adalah kalibrasi alat instrumen nuklir untuk terapi, terdiri dari kalibrasi dosimeter dan luaran radioterapi. Pada awal tahun 2020, fasilitas kalibrasi dosimeter harus diperbaharui. Pergantian sumber Co-60 telah dilakukan dengan menggunaan sumber baru. Tetapi, sumber baru tersebut merupakan sumber Co-60 hasil pemakaian kembali dari sumber bekas yang berasal dari limbah rumah sakit. Makalah ini mendiskusikan parameter dosimetri dari pemakaian kembali sumber Co-60 sebagai pesawat kalibrator. Pengukuran data terdiri dari pengukuran kesalahan pewaktu, profil berkas radiasi, laju dosis radiasi pada besaran Kerma udara, dan dosis serap air, dan stabilitas peluruhan. Referensi yang digunakan adalah publikasi IAEA TRS No. 469. Semua pengukuran dilakukan dengan menggunakan detektor ionisasi standar. Hasil kesalahan pewaktu menunjukkan adanya penundaan waktu selama -2.52 detik setelah tombol mesin dinyalakan. Laju Kerma udara didapatkan sebesar 230,15 µGy/menit, sedangkan untuk laju dosis serap air didapatkan 211,08 mGy/menit. Aktifitas sumber didapatkan sebesar 51,4 TBq pada 07 Desember 2020. Hasil peluruhan aktifitas dan laju dosis masih dalam rentang yang diterima. Aktifitas harus pada 20 -40 TBq, sedangkan untuk laju dosis harus melebihi 100 mGy/menit pada jarak 1 meter pengukuran. Stabilitas pengukuran dilakukan pada peluruhan laju dosis, dan dijaga pada deviasi satu persen. Berdasarkan hasil tersebut, pemakaian kembali mesin Co-60 telah siap untuk digunakan sebagai mesin kalibrator pada fasilitas sinar gamma.